Snow crab (Chionoecetes opilio) in the Barents Sea. Possibility of harvesting a new species by the Russian Fleet - Sherstneva, Aleksandra (UiT The Arctic University of Norway, 2013)
Snow crab (Chionoecetes opilio) is a small crab of a high commercial value, with delicious and nutricious meat. In the global market, it is a popular marine product. As a rule, snow crab is sold frozen in limb sections or as separate meat. The product price is difficult to define as it depends on a price for the exported snow crab, on the currency rate, meat quality and economic situations in importing those countries. States, which harvest this type of crab, suppose this business to be economically efficient, but certainly with an appropriate management only. Snow crab is distributed in the North-Western Atlantic Ocean and in the Northern Pacific Ocean. Recently this species was found in the northeastern part of the Atlantic Ocean, too, namely in the Barents Sea. There are two main versions of its appearance. Scientists assume, that it appeared in the Barents Sea with ballast waters from the North-Western Atlantic. Another version is that it crawled from the Far-Eastern Seas such as the Sea of Okhotsk, the Bering Sea, etc. More likely, that it occurred in the Barents Sea with ballast waters. In this case, it is considered an invasive species. Consequently, it should be destroyed as soon as possible, because its further distribution may influence negatively the new environment and ruin the balance of the ecosystem. In the thesis, I describe the snow crab biology and its basic behavioural characteristics in order to find out if the new ecosystem of the Barents Sea is appropriate enough for the species. Hereafter, I use data about red king crab (Paralithodes camtschaticus) in the Barents Sea as an example of invasive species. This action is aimed at the estimation of possible consequences of the migration. In addition, in the subsection about red king crab in the Barents Sea I mention some management measures connected with its harvesting. Usage of this experience might be helpful when making recommendations concerning the snow crab fishery in Russia. Finally, the Barents Sea itself is described with the purpose ...